Permanent fore‐arc extension and seismic segmentation: Insights from the 2010 Maule earthquake, Chile. Issue 2 (26th February 2013) - Aron, Felipe; Allmendinger, Richard W.; Cembrano, José; González, Gabriel; Yáñez, Gonzalo
Abstract : [1] Geologists have long known that young normal faults are an important structural element of the Andean Coastal Cordillera, but their relationship to the subduction seismic cycle is still unclear. Some of the largest aftershocks of the 2010 Mw  8.8 Maule earthquake in central Chile were nucleated on upper plate normal faults, including the Mw  6.9 and 7.0 events of the Pichilemu earthquake sequence. We use the available coseismic GPS displacements, moment tensor sums, and slip distribution models for the Maule earthquake to compute the static strain and stress fields imposed on the upper plate by slip on the subduction interface. The extensional strains calculated from coseismic GPS and from a moment tensor sum of the Pichilemu events have similar orientations and orders of magnitude. The normal Coulomb stress increment (CSI) on the Pichilemu fault has maximum positive stresses as high as 4.9 MPa. Regionally, the Maule event produced a semi‐elliptical, radial pattern of static extension and deviatoric tension (CSI > 1.5 MPa) along the Coastal Cordillera enclosing the rupture area. This elliptical pattern mimics the trends of the major upper‐crustal structures. The static deformation field produced by a great subduction earthquake is an effective mechanism for generating permanent extension above the seismogenic zone, reactivating suitably oriented, long‐lived normal faults. We suggest that the semi‐elliptical outline of the first‐order structures along the Coastal Cordillera may define the location of a characteristic, long‐lived megathrust segment. This observation implies a persistence at least over the Quaternary of great subduction ruptures along the Maule segment. Key Points: Great subduction earthquakes generate permanent upper plate extension Genetic relation between the seismic cycle and the fore‐arc structural grain Upper plate structures may be used to identify long‐lived subduction segments